PP.19.18: EFFECTS OF DIPEPTIDYL PEPTIDASE 4 INHBITION ON URINARY ALBUMIN EXCRETION IN TYPE 2 DIABETIC HYPERTENSIVE PATIENTS. (June 2015) - Ruiz-Roso, G.; Guerrero, L.; Fernandez, L.; Ruiz, G.; Praga, M.; Ruilope, L.M.; Segura, J.
Abstract : Objective: Inhibitors of dipeptidyl peptidase 4 (DPP-4) are a new class of antidiabetic drugs that inhibit DPP4 enzyme that degrades the type 1 glucagon-like peptide (GLP-1). Some studies have shown that GLP-1 slows the progression of diabetic nephropathy. However, there is little information on the effect of these drugs on urinary albumin excretion (UAE) in diabetic patients. This paper analyzes the changes in UAE related to the administration of vildagliptin in patients with type 2 diabetes and essential hypertension. Design and method: 106 type 2 diabetic patients, 44% men were included, with a mean age of 67.7 ± 9.3 years, all treated hypertensive patients followed, with available clinical and laboratory information at least six months before and six months after initiation of treatment with vildagliptin. They were classified according to the albumin-to- creatinine ratio (ACR) in normo- (ACR < 30 mg/g) (n = 69), micro- (ACR 30–300 mg/g) (n = 25) and macroalbuminuric (ACR>300 mg/g) (n = 12). Results: The table describes the changes in the UAE by logarithmic transformation in the three subgroups. Figure. No caption available. Before vildagliptin, micro- and macroalbuminuric patients show a progressive increase in the UAE, which remains after adjust for systolic BP. After addition of the drug, patients with microalbuminuria show a progressive decrease in the UAE, which remains after correcting for changes in systolic BP. The macroalbuminuric patients also show a progressive decrease in the UAE, although it seems that changes in systolic BP would justify such changes. Normoalbuminuric patients maintain no significant changes in UAE before and after vildagliptin. Conclusions: In conclusion, the UAE tends to progress over time in type 2 diabetic patients with micro- or macroalbuminuria regardless of blood pressure. Vildagliptin added as an antidiabetic treatment may help to slow this progression.